Case Study Based on Inequality Indices for the Assessments of Industrial Fleets - Orchard-Rieiro, M (Elsevier B.V., 2016)
This contribution illustrates the advantages of measures and indicators based on the notions of Shannon entropy which is widely implemented in thermodynamics, information theory, econometrics, and biology. The presented case study applies these indicators to a fleet of industrial assets, introducing innovatively the entropy concept to the field of availability. There is no reason to deal the effect of performance variables in assets independently without taking into account disparities in terms of reliability, operation hours, applied maintenance, operating conditions, and usage profiles, etc. Therefore, the characteristic of the method and their independence from the heterogeneity of the sample that compares is intended to be promising for applications in availability analysis. In other words, this research presents a derivation from well-known concepts such as the Gini, Hoover and Theil indices illustrating their application by the support of an example where attributes for different groups of assets are compared. To illustrate the application we are using two relevant and innovative scenarios as case study examples. © 2016